PENINGKATAN LITERASI MEMBACA PEMAHAMAN MELALUI BUKU CERITA BERBASIS FLIPBOOK PADA SISWA KELAS II SEKOLAH DASAR - Dwi Masitha, Amalia; Rahayu, Sri; Sa’diyah, Halimatus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension literacy is an important skill that should be developed in elementary school to help students understand information and build knowledge. However, observations in the second grade of SDN Karangbesuki 2 Malang showed that many students still had difficulty understanding the texts they read, even though most of them could read fluently. This study aimed to improve students’ reading comprehension literacy through the use of flipbook-based storybooks. The research used the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles with the stages of planning, action, observation, and reflection. The participants were 23 second-grade students of SDN Karangbesuki 2 Malang. Data were collected through tests, observations, interviews, and documentation and analyzed using descriptive quantitative and qualitative methods. The results showed that students’ classical learning mastery increased from 30.43% in the pre-cycle to 60.87% in Cycle I and 86.96% in Cycle II. Teacher and student activities during the learning process also improved and reached the “very good” category. Therefore, the use of flipbook-based storybooks was effective in improving the reading comprehension literacy of second-grade elementary school students.